D-A-D-based unsymmetrical thiosquaraine dye for the dye-sensitized solar cells(dagger) - Jadhav, Avinash P.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemistry and Photobiology, 2023)
In dye-sensitized solar cell, modulating the electronic properties of the sensitizer by varying the donor, pi-spacer, acceptor and anchoring groups help optimizing the structure of the dye for better device performance. Here, a donor-acceptor-donor-based unsymmetrical thiosquaraine sensitizer (SQ5S) has been designed and synthesized. Photophysical, electrochemical, theoretical and photovoltaic characterizations of SQ5S dye have been compared with its oxygen analog, SQ5. The incorporation of the sulfur atom in the acceptor unit of SQ5S dye showed an intense peak at 688 nm, which was 38 nm of red-shifted and showed the panchromatic light harvesting response with the onset of 850 nm compared with SQ5 dye. The LUMO and HOMO energy levels are well aligned with the conduction band of TiO2 and the redox potential of electrolyte for the charge injection and the dye-regeneration processes, respectively. Photovoltaic efficiency of 1.51% (V-OC 610 mV, J(SC) 3.07 mA cm(-2), ff 81%) has been achieved for SQ5S dye, whereas SQ5 showed the device performance of 5.43% (V-OC 723 mV, J(SC) 9.3 mA cm(-2), ff 80%). The decreased device performance for the dye SQ5S has been attributed to the favorable intersystem crossing process associated with the photoexcited SQ5S that reduces the driving force for the charge injection process.